Neuropsychiatric lupus or not? Cerebral hypoperfusion by perfusion-weighted MRI in normal-appearing white matter in primary neuropsychiatric lupus erythematosus. Issue 3 (19th December 2017) - Papadaki, Efrosini; Fanouriakis, Antonis; Kavroulakis, Eleftherios; Karageorgou, Dimitra; Sidiropoulos, Prodromos; Bertsias, George; Simos, Panagiotis; Boumpas, Dimitrios T
Abstract : Objectives: Cerebral perfusion abnormalities have been reported in systemic lupus erythematosus (SLE) but their value in distinguishing lupus from non-lupus-related neuropsychiatric events remains elusive. We examined whether dynamic susceptibility contrast-enhanced perfusion MRI (DSC-MRI), a minimally invasive and widely available method of cerebral perfusion assessment, may assist neuropsychiatric SLE (NPSLE) diagnosis. Methods: In total, 76patients with SLE (37 primary NPSLE, 16 secondary NPSLE, 23 non-NPSLE) and 31 healthy controls underwent conventional MRI (cMRI) and DSC-MRI. Attribution of NPSLE to lupus or not was based on multidisciplinary assessment including cMRI results and response to treatment. Cerebral blood volume and flow were estimated in 18 normal-appearing white and deep grey matter areas. Results: The most common manifestations were mood disorder, cognitive disorder and headache. Patients with primary NPSLE had lower cerebral blood flow and volume in several normal-appearing white matter areas compared with controls (P<0.0001) and lower cerebral blood flow in the semioval centre bilaterally, compared with non-NPSLE and patients with secondary NPSLE (P<0.001). A cut-off for cerebral blood flow of 0.77 in the left semioval centre discriminated primary NPSLE from non-NPSLE/secondary NPSLE with 80% sensitivity and 67%–69% specificity. Blood flow values in the left semioval centre showed substantially higher sensitivity than cMRI (81% vs 19%–24%) for diagnosing primary NPSLE with the combination of the two modalities yielding 94%–100% specificity in discriminating primary from secondary NPSLE. Conclusion: Primary NPSLE is characterised by significant hypoperfusion in cerebral white matter that appears normal on cMRI. The combination of DSC-MRI-measured blood flow in the brain semioval centre with conventional MRI may improve NPSLE diagnosis.